2016
DOI: 10.3892/ijo.2016.3788
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LAPTM5 suppresses cell proliferation and viability inducing cell cycle arrest at G0/G1 phase of bladder cancer cells

Abstract: Our transcriptome analysis revealed in bladder cancer (BCa) tissues a significant induction of lysosomal-associated multispanning membrane protein 5 (LAPTM5), a lysosomal membrane protein preferentially expressing in immune cells and hematopoietic cells. Transportation of LAPTM5 from Golgi to lysosome could be inhibited by deficiency of Nedd4, a key member of E3 ubiquitin ligase family overexpressing in invasive BCa and promoting its progression. Therefore, we hypothesize that LAPTM5 may be closely correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Recent studies suggested that HJURP participated in the regulation of cell immortality in lung cancer 10 and breast cancer 11 , and could be a new independent prognostic marker for breast cancer 12 - 14 , indicating an important role of HJURP in human diseases 15 . Though the correlation between HJURP and bladder cancer has not been investigated yet, our transcriptome data 3 , 4 , 16 suggested that HJURP was involved in nucleosome assembly and cell cycle regulation in BCa. Our recent works showed that induction of cell cycle arrest could inhibit proliferation of urological cancer cells 17 - 19 .…”
Section: Introductionmentioning
confidence: 82%
“…Recent studies suggested that HJURP participated in the regulation of cell immortality in lung cancer 10 and breast cancer 11 , and could be a new independent prognostic marker for breast cancer 12 - 14 , indicating an important role of HJURP in human diseases 15 . Though the correlation between HJURP and bladder cancer has not been investigated yet, our transcriptome data 3 , 4 , 16 suggested that HJURP was involved in nucleosome assembly and cell cycle regulation in BCa. Our recent works showed that induction of cell cycle arrest could inhibit proliferation of urological cancer cells 17 - 19 .…”
Section: Introductionmentioning
confidence: 82%
“…Our group has revealed a variety of potential biomarkers 32,38,39 based on transcriptome data of normal bladder tissues vs BCa which has been demonstrated to play a crucial role in cancer cell invasion and migration. 52 The association of vimentin and cytokeratin was also revealed in the transitional cell carcinoma genesis of urinary bladder patients, and thus could be a favourable marker in the early diagnosis of transitional BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has revealed a variety of potential biomarkers 32,38,39 based on transcriptome data of normal bladder tissues vs BCa tissues. 34,41 Most of them are related to the PPAR signalling pathway, which could represent a connection between fatty acid/lipid metabolism and BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal-associated protein multispanning transmembrane 5 (LAPTM5) is a membrane protein that localizes to intracellular vesicles. LAPTM5 mRNA level is frequently decreased in various cancer cell lines [28]. Overexpression of LAPTM5 in cancer cells induces lysosomal cell death due to lysosomal destabilization [29].…”
Section: Discussionmentioning
confidence: 99%